The role of livestock farming groups in developing the empowerment of beef cattle fattening business in the Cirebon Regency - Fitri Dian Perwitasari; Bayu Arisandi; Ahmad Romadhoni Surya Putra; Bambang Suwignyo; Rini Widiati (Universitas Sebelas Maret, 2022)
Objective: The research is as follows: (1) The role of the farmer group in its function as a place of learning, a place of production, and a place for cooperation and member business, (2) the empowerment of beef cattle farmers, and (3) the relationship between the role of the group and the empowerment of beef cattle farmers in Cirebon Regency.Methods: I conducted this research from July to August 2021. The research method was survey and field observation—data analysis using SPSS 26 Spearman rank correlation test. The number of respondents using the Snowball sampling formula is 60 respondents from 5 livestock farmer groups in Cirebon Regency.Results: The empowerment of farmers in this study measures two aspects: farmers' ability to maintain and have high-value entrepreneurship. The correlation coefficient of the relationship between the part of the group and the empowerment of beef cattle farmers is 0.674. In conclusion, the relationship is quite strong between the two variables. The role of the group is not optimal either as a place of learning, a place of business, or a place to work together, which requires the involvement of the Cirebon Regency agriculture office, educational institutions, and private institutions to be involved in developing the role of groups in Cirebon Regency.Conclusions: The empowerment of farmers in this study measures aspects, namely, 1) the role of the group is not optimal, while 2) the ability of farmers to maintain entrepreneurship is of high value. The correlation coefficient of the relationship between the role of the group and the empowerment of beef cattle farmers is 0.674. It indicated that the relationship is quite strong between the two variables.